Influence of process parameters on dimensional accuracy of machined Titanium (Ti-6Al-4V) alloy in Laser Beam Machining Process. (December 2020) - Muthuramalingam, T.; Moiduddin, Khaja; Akash, Ravi; Krishnan, Shravan; Hammad Mian, Syed; Ameen, Wadea; Alkhalefah, Hisham
Highlights: Power has the most influential impact on determining the geometrical accuracy. Optimal parameters provide lower plasma energy and uniform distribution. Power and gas pressure influences entry and exit hole diameter. Power and nozzle distance influences entry and exit hole roundness. Abstract: The process enhancement plays a vital role in the modern machining techniques during machining of newer materials such as titanium alloys. In the present work, a research endeavor was made to examine the effects of process parameters in laser beam machining process while drilling holes over Titanium (Ti-6Al-4V) alloy under Taguchi approach of experiments. Nozzle distance, power, focal length and gas pressure were chosen as the input process parameters to assess the dimensional accuracy quality measures such as roundness and ovality in laser beam machining process. It was found that power has the most significant impact on determining the dimensional accuracy. 1.2 mm (ND), 2 mm (L), 4 bar (GP) and 2 kW (J) has been chosen as optimal process parameters combination for obtaining better dimensional accuracy among the selected process parameters. It was also observed that the machinability could be highly influenced with lower peak power.